Antimicrobial Resistance in Bacteria Isolated From Cats and Dogs From the Iberian Peninsula - Li, Yanli; Fernández, Rubén; Durán, Inma; Molina-López, Rafael A.; Darwich, Laila (Frontiers in Microbiology, 2021)
Pet animals are assumed to be potential reservoirs in transferring antimicrobial resistance (AMR) to humans due to the extensively applied broad-spectrum antimicrobial agents and their close contact with humans. In this study, microbiological data and antimicrobial susceptibility results of dog (n=5086) and cat (n=789) clinical samples from a private Laboratory of Diagnosis in Barcelona were analyzed. Samples came from different counties of the Iberian Peninsula during 2016-2018. In dogs, clinical samples were most commonly from otitis, and in cats from wounds, respiratory tract infections and conjunctivitis. In both pet groups, Staphylococcus spp (31% in dogs vs 30% in cats), Streptococcus spp (19% vs 17%), Pseudomonas spp (16% vs 10%), Escherichia coli (8% vs 5.6%), and Enterococcus spp (5.5% vs 6.8%) were shown as the most predominant bacteria. However, higher frequencies of P. aeruginosa, P. canis and S. pseudintermedius were found in dogs, while S. aureus and P. multocida were more prevalent in cats. The antimicrobial susceptibility testing demonstrated that Enterococcus spp and Pseudomonas spp presented the highest levels of AMR in both dogs and cats. Within the Enterobacteriaceae, E. coli showed low levels of AMR compared to Klebsiella, Proteus or Enterobacter spp. Respiratory tract infections caused by K. pneumoniae presented higher AMR in cats. By contrast, Pasteurella isolates from the respiratory tract were highly sensitive to all the antimicrobials in cats and dogs. Data from this study could be used to guide empirical antimicrobial selection in companion animal veterinary practices in the Iberian Peninsula.